Teachers’ Opinions on Inclusive Education - Ketenoğlu Kayabaşı, Zehra Esra (Bilge Akademi, 2020)
The aim of this research is to determine the opinions of teachers working in the city of Kastamonu towards inclusive education and to investigate what inclusive education practices are. For this purpose this research was conducted from a qualitative perspective. The study group consists of thirteen teachers from various branches working in the province of Kastamonu. While collecting data, the semi-structured questionnaire form of the correspondence technique, which is one of the qualitative data collection techniques, was used. The questionnaire consists of two parts, including the Personal Information Form and questions related to the purpose of the research. The responses of the participants to the teacher correspondence questionnaire were evaluated in the context of the content and the findings of the study were collected in five dimensions; inclusive education approach, what teachers should do, teacher practices, school policies to be applied and policies to be applied across the country. In the research, it was observed that teachers had a general idea about inclusive education, but they were also associated with the education of people with disabilities. Teachers mostly stated that they provided education according to individual differences. They stated that the physical environment should be regulated in schools and in-service trainings should be provided nationwide.
Keywords: 4. Education; 10. No inequality